CHARACTER EDUCATION IN ISLAMIC HIGHER EDUCATION - Cahaya (International Journal of Teaching and Learning, 2025)
This research aims to explore the concept, implementation and challenges of character education in Islamic higher education. Through an in-depth literature review, this research identifies that character education in Islamic universities does not only focus on academic achievement, but also on the formation of strong morality and ethics. Islamic universities utilize Islamic values as the main foundation in educating students to become individuals with integrity, morals, and able to contribute positively to society. However, this research also revealed a number of significant challenges, including limited resources, lack of training for lecturers, diversity of student cultural backgrounds, time constraints, and difficulties in measuring character development. Literacy related to curriculum development strategies, lecturer training, and character evaluation methods is the key to overcoming this challenge. Character education in Islamic higher education requires the commitment of all parties involved, from institutional leaders to students, to achieve optimal results. This research concludes that with a holistic and integrative approach, Islamic higher education has great potential to produce graduates who are not only academically superior but also have noble character.